Embedding Ultrasmall Au Clusters into the Pores of a Covalent Organic Framework for Enhanced Photostability and Photocatalytic Performance. (20th February 2020) - Deng, Yang; Zhang, Zhen; Du, Peiyao; Ning, Xingming; Wang, Yue; Zhang, Dongxu; Liu, Jia; Zhang, Shouting; Lu, Xiaoquan
Abstract: Gold clusters loaded on various supports have been widely used in the fields of energy and biology. However, the poor photostability of Au clusters on support interfaces under prolonged illumination usually results in loss of catalytic performance. Covalent organic frameworks (COFs) with periodic and ultrasmall pore structures are ideal supports for dispersing and stabilizing Au clusters, although it is difficult to encapsulate Au clusters in the ultrasmall pores. In this study, a two‐dimensional (2D) COF modified with thiol chains in its pores was prepared. With −SH groups as nucleation sites, Au nanoclusters (NCs) could grow in situ within the COF. The ultrasmall pores of the COF and the strong S−Au binding energy combine to improve the dispersibility of Au NCs under prolonged light illumination. Interestingly, Au–S–COF bridging as observed in this artificial Z‐scheme photocatalytic system is deemed to be an ideal means to increase charge‐separation efficiency. Abstract : Brücken bauen : Die Poren eines kovalenten organischen Gerüsts (COF) wurden mit Thiolketten als Nukleationsstellen für Goldnanocluster (NCs) modifiziert. Die Au‐S‐COF‐Brücken im resultierenden Photokatalysator erhöhten die Effizienz der Ladungstrennung. Zudem verbessern die ultrakleinen Poren und die starke S‐Au‐Bindungsenergie die Dispergierbarkeit der Au‐NCs und ihre Photostabilität bei längerer Belichtung.